Insect elevational specialization in a tropical biodiversity hotspot. Issue 3 (11th October 2017) - Macedo, Margarete V.; Monteiro, Ricardo F.; Flinte, Vivian; Almeida‐Neto, Mario; Khattar, Gabriel; da Silveira, Luiz F. L.; Araújo, Cristina de O.; Araújo, Rodrigo de O.; Colares, Carolina; Gomes, Carlos V. S.; Mendes, Clarice B.; Santos, Eduardo F.; et al.
Abstract: Tropical montane organisms are vulnerable to climate change because of elevational specialisation, but little is known of the variability in elevational specialisation across tropical insects. We assessed elevational specialisation across several insect taxa comprising four trophic groups 80–2263 m up an elevational transect in Brazilian Atlantic Rainforest, using community‐based and species‐based approaches. We sampled 697 species, of which 32% were found only in the top and 45% only in the bottom half of the transect. Considering only the 182 species with at least five individuals recorded, the percentage of species found exclusively in the top or bottom half drops to 16% and 24%. Across four vegetation belts (lower montane forest, montane forest, upper montane forest and Campos de Altitude) the Eumolpinae (herbivores) were more specialised than Scarabaeinae (saprotrophs), or Lampyridae (predators). This result was robust to the treatment of rare species, and the difference was most marked at higher elevations. Lampyridae lacked upper montane forest specialists. Using all species sampled, specialisation to the upper or lower half of the transect was greatest among Chrysomelidae, Curculionidae (both herbivores) and Lampyridae, and lowest among Tiphiidae (parasitoids) and Coccinellidae (predators). Considering only better sampled species, however, Lampyridae were the most specialised and Braconidae the least specialised. Trophic groups also varied consistent with these findings. Our findings suggest high elevational specialisation and concomitant extinction risk in Brazilian Atlantic Rainforest insects. Differences in elevational specialisation between taxonomic groups may alter the functioning of insect communities under climate change.